2009
DOI: 10.1093/hmg/ddp073
|View full text |Cite
|
Sign up to set email alerts
|

Use of a genetic isolate to identify rare disease variants: C7 on 5p associated with MS

Abstract: Large case–control genome-wide association studies primarily expose common variants contributing to disease pathogenesis with modest effects. Thus, alternative strategies are needed to tackle rare, possibly more penetrant alleles. One strategy is to use special populations with a founder effect and isolation, resulting in allelic enrichment. For multiple sclerosis such a unique setting is reported in Southern Ostrobothnia in Finland, where the prevalence and familial occurrence of multiple sclerosis (MS) are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…It contains complement component 7 (C7), again an important factor in the innate immune system (84). These results exemplify the power of population isolates in the identification of rare disease alleles .…”
Section: Accepted M Manuscriptmentioning
confidence: 86%
“…It contains complement component 7 (C7), again an important factor in the innate immune system (84). These results exemplify the power of population isolates in the identification of rare disease alleles .…”
Section: Accepted M Manuscriptmentioning
confidence: 86%
“…Examples of this abound in human populations, especially for Mendelian diseases of recessive inheritance, such as lysosomal storage diseases [Risch et al, ], cystic fibrosis [Fares et al, ], and glycogen storage disease [Ekstein et al, ]. For complex diseases, the impact of founder effects and population bottlenecks is less clear regarding prevalence, but the distortion of risk allele frequencies is still an expected outcome and can be useful for gene mapping [Kallio et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…C7 is primarily synthesized extrahepatically at the site of inflammation by granulocytes (Høgåsen et al, 1995) and endothelial cells (Tedesco et al, 1997), thereby modulating lytic or sublytic membrane attack (Würzner, 2000;Langeggen et al, 2000). A number of studies have reported that variations in C7 play an important role in the resistance to a variety of diseases in humans (Kallio et al, 2009;Barroso et al, 2010). To date, at least 25 different sequence variants have been reported that can lead to C7 deficiency (RameixWelti et al, 2007).…”
Section: Discussionmentioning
confidence: 99%